Novas abordagens na síntese de heterociclos com potencial aplicação na síntese de moléculas bioativas - Alves, Tânia Mara Ferreira (2017)
Cobalt-catalyzed oxidative cyclization of gem-disubstituted conjugated alkenols: In this part of the work we applied the Mukaiyama Oxidative Ciclization under oxidative and reduced termination conditions aiming the preparation of trisubstituted 2,5,5-THFs-trans from gemdisubstituted aromatic conjugated olefins with different electronic properties. The THFs were obtained only under reduced termination conditions, with of 32-44% of yields. Under oxidative termination conditions, only products from secondary radical reactions that competed with the oxidative cyclization reaction were observed. In addition, the diastereoselectivity involved in this process was evaluated,, which in this case were obtained in 17-46% of yields and dr 2.5:1 to 5.4: 1. Preparation of 1H-1,2,3-triazole under more sustainable conditions: In this second part of the work the main objective was to develop an one-pot methodology for the preparation of 1H-1,2,3-triazoles from nitrolefins. This methodology is inserted in a concept of a more sustainable chemistry, since the obtaining heterocyclics was carried out through a metal-free approach, using the green solvent PEG400, and the direct use of sodium azide. The 1H-1,2,3-triazoles were obtained via one-pot reaction in good yields (54-80%).